MEMPROGRAMKAN PENGENALAN MANAJEMEN ZAKAT INFAQ SHODAQOH DI DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Bayu Purnama Putra; Andriyansyah (SAHID EMPOWERMENT JOURNAL, 2022)
This community service aims to introduce the management of zakat, infaq and shodaqoh so that people can know the benefits and uses of zakat, infaq and shodaqoh to develop the economy in their area. The subject of this community service is the people of Ciaruteun Ilir Village, Cibungbulang District, Bogor Regency, West Java Province. In this community service activities are carried out based on survey methods, counseling and outreach, as well as evaluation of activities. The result of this community service is that people can better understand and know the benefits of zakat, infaq and shadaqoh and know that zakat can be used for productive business activities managed by the zakat recipients themselves. With this community service, it can be concluded that zakat is an obligation that must continue to be preserved in order to achieve a society that is able to be independent and avoid hardship, besides of course it is an obligation in Islam. Infaq and shodaqoh remind us that some of the assets we have today have other people's rights that we must give. Thus, the community has a thorough understanding of zakat, infaq and shodaqoh.